Application of Carbon Nanotubes as Drug Delivery System for Anticancer Therapy - Shrestha, Sabita (Curriculum Development Journal, 2020)
Carbon nanotubes are one-dimensional allotrope of carbon having high aspect ratio, high surface area, and excellent material properties. It has applications in many fields such as catalyst, nano-electronics, field emission, nano medicine, solar cells, energy storage etc. Drug delivery is one of the important applications of carbon nanotubes because of its unique properties such as high drug loading capacity, thermal ablation, ease of cellular uptake. This article briefly overviews the different steps in drug delivery and anticancer therapy such as mechanism of drug loading, transportation, distribution, metabolism and finally excretion of drug.